NATURAL HYBRIDIZATION AMONG COCKSFOOT (DACTYLIS GLOMERATA) SUBSPECIES IN GALICIA (NORTHWEST SPAIN) - Lindner, R.; Lema, M.; Lindner, G.; García, A. (Pastos, 2011)
Special cocksfoot (Dactylis glomerata L.) ecotypes from Galicia (Spain) were compared with D. glomerata subsp. hispánica from Portugal, in order to determine if they belonged to that Mediterranean subspecies, which was not observed in Galicia to date (because of its Atlantic influence). Although multivariate analysis of quantitative traits separated subsp. hispánica from Galician cocksfoot, allelic frequencies of the diagnostic isozyme locus SOD1 (TOl) related subsp. hispánica to Mgll49, a natural population near Casaio (in the Southeast of Galicia, with Mediterranean climate). It is concluded that this population is a hybrid between subsp. hispánica and subsp. izcoi (an endemic subspecies of Galicia and north of Portugal), both tetraploids. The other populations from this zone present a genic flux from subsp. hispánica.